2018
DOI: 10.1186/s12901-018-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns of bacteria isolated from patients with ear discharge in Jimma Town, Southwest, Ethiopia

Abstract: BackgroundOtitis media is among the leading causes of childhood illnesses although it can also affect the adults resulting in frequent physician visits, drug prescription and a key contributor to antibiotic resistance. The aim of this study was to determine the risk factors, bacterial profile, and the antimicrobial susceptibility pattern of the isolates from patients with discharging ears which clinically equates to draining otitis media in developing countries with limited medical resources such as otoscope.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 24 publications
6
12
1
Order By: Relevance
“…In the present study all bacterial isolates showed low level of resistance to ciprofloxacin (0-6.9%), and gentamicin (0-29.6%).This result is in agreement with the study by other authors in Africa where 0-33% and 0-37.5% level of resistance were reported against ciprofloxacin and gentamicin, respectively [4,19].Gram negative species of the present study also revealed low level of resistance against ceftazidime, ceftriaxone and cefotaxime. This was comparable with previous report in Ethiopia [38].…”
Section: Plos Onesupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study all bacterial isolates showed low level of resistance to ciprofloxacin (0-6.9%), and gentamicin (0-29.6%).This result is in agreement with the study by other authors in Africa where 0-33% and 0-37.5% level of resistance were reported against ciprofloxacin and gentamicin, respectively [4,19].Gram negative species of the present study also revealed low level of resistance against ceftazidime, ceftriaxone and cefotaxime. This was comparable with previous report in Ethiopia [38].…”
Section: Plos Onesupporting
confidence: 92%
“…The overall MDR rate of Gram negative isolates in this study (43%) was lower than studies done in Mekele (74.5%) [12]and Jimma (67%) [4],Ethiopia. This might be due to variations in the classes of antibiotics, MDR definition, specimen type and study participants.…”
Section: Plos Onecontrasting
confidence: 80%
See 2 more Smart Citations
“…(Table -1 These observations are in contrast to the other studies showing higher sensitivity of 90 -92%. 13 The declining sensitivity trend with quinolones may be due to a number of factors including injudicious use, inappropriate dosage, and easy accessibility.…”
Section: Resultsmentioning
confidence: 99%